2021
DOI: 10.1029/2020ja028925
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter's Ion Radiation Belts Inward of Europa's Orbit

Abstract: Jupiter has the largest magnetosphere in the solar system and electron radiation belts with the highest energies (Mauk & Fox, 2010;. It has been visited by several spacecraft (Krupp et al., 2004), yet there are regions in physical space and particle energy that are not well explored (Roussos et al., 2019). High intensities of either electrons or protons can impact the integrity of in-situ radiation measurements Mauk et al., 2016;Nénon, Sicard, Caron et al., 2018), which becomes an issue inward of the orbit of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 69 publications
(147 reference statements)
1
27
0
Order By: Relevance
“…range of first adiabatic invariant μ (Paranicas et al, 1990). The ion PSD profiles derived from the Juno observations within Europa's (M ∼ 9.5) orbit were analyzed and used to indicate a source of inner belt ions coming from inward radial transport (Kollmann et al, 2021). A recent study that extended to radial distances of M = 25 showed an almost continuously increasing radial PSD as M-shells increase at energies above 1,000 MeV/G (Garrett & Jun 2021).…”
mentioning
confidence: 99%
“…range of first adiabatic invariant μ (Paranicas et al, 1990). The ion PSD profiles derived from the Juno observations within Europa's (M ∼ 9.5) orbit were analyzed and used to indicate a source of inner belt ions coming from inward radial transport (Kollmann et al, 2021). A recent study that extended to radial distances of M = 25 showed an almost continuously increasing radial PSD as M-shells increase at energies above 1,000 MeV/G (Garrett & Jun 2021).…”
mentioning
confidence: 99%
“…Jupiter is well known to have the largest magnetosphere in the solar system and electrons radiation belts with the highest energies (e.g., Mauk & Fox, 2010;. Surrounded by intense and energetic radiation belts, the radiation conditions of Jupiter are more extreme inside the Europa's orbit than outside regions (e.g., Kollmann et al, 2017Kollmann et al, , 2021Woodfield et al, 2014). Six moons orbit around Jupiter inside L < 10 (Metis: Φ = 40 km, L = 1.84, and e m = 0.0077; Adrastea, Φ = 16 km, L = 1.84, and e m = 0.0063; Amalthea: Φ = 167 km, L = 2.59, and e m = 0.0075; Thebe: Φ = 98 km, L = 3.17, and e m = 0.018; Io: Φ = 3,637.4 km, L = 6.01, and e m = 0.0041; Europa: Φ = 3,121.6 km, L = 9.57, and e m = 0.009).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Due to the absorption loss by Europa, the particle fluxes can also exhibit a minimum around this orbit. Interestingly, absorption at Europa mostly shows for >10 MeV ions(Kollmann et al, 2021) and otherwise only affects particles in its immediate vicinity (e.g.,Paranicas et al, 1998;Kollmann et al, 2018), even though absorption times are smallest for the lowest energies. The reason for this is likely the competition between absorption and other processes that resupply energetic particles at low energies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The precise determination of τ loss is highly non-trivial. Such modeling may benefit from matching with other in situ data such as the fluxes of non-relativistic ions [92] or magnetic fields [93]. We will not pursue an accurate modeling of τ loss in our paper.…”
Section: Scenarios Beyond the Dipole Approximationmentioning
confidence: 99%